Design, Construction and Validation of an Electrical Impedance Probe with Contact Force and Temperature Sensors Suitable for in-vivo Measurements. Issue 1 (December 2018) - Ruiz-Vargas, Albert; Ivorra, Antoni; Arkwright, John
Abstract Bioimpedance spectroscopy measurements can be used for tissue characterization. These measurements can be performed in soft tissues by direct contact of a non-invasive probe consisting of two or four electrodes. The amount of force applied by users can be quite different, and the measurements can vary as a result. To compensate for this, we have built an electrical impedance probe (diameter 3.2 mm) with fibre optic contact-force and temperature sensors built in it. The different sensors of the probe were tested individually. The errors in magnitude and phase angle of the probe are <0.9% and <4°, respectively, for a 0.9% NaCl solution. The linear dynamic range of the force sensor was from 0 to 100 grams. Anex-vivo experiment on a section of proximal colon from a guinea-pig was performed. Twenty bioimpedance measurements were taken in a frequency range of 5 kHz to 1 MHz, while simultaneously recording the force applied. For an increase in contact pressure applied to tissue from 0 to 15.4 kPa, the maximum change in resistivity was 33% at 5 kHz and the minimum was 6.6% at 142 kHz. The probe is small enough to be introduced via the instrument port of an endoscope.